Focus on the USA. - Schneider, Edgar W. (Varieties of English around the world. General series ;, 1996)
This volume presents 15 original research papers by renowned specialists in their respective fields. A variety of research traditions are included, such as dialect geography and sociolinguistics, but also smaller sub-fields such as the study of slang and perceptual dialectology. Varieties studied include the South, the Eastern Seaboard, the Middle West, African American English, Cuban English, and others. A growing sense of unity in the discipline is reflected by recurring topics and methods across earlier boundaries between sub-disciplines. For instance, computerized data and statistical analyses are standard tools nowadays, and a few papers explicitly address the possibilities and limitations of these methods. The study of variation and change of linguistic varieties has largely replaced earlier, monolithic notions of dialect, and the question of change in dialects, the erosion of traditional speech forms under the impact of modern communication patterns and socio-economic developments, is investigated in several contributions. In general, a recent orientation towards the history and development of nonstandard varieties is reflected in the book - several papers study diffusion patterns of linguistic forms, or discuss the emergence of individual dialects or dialectal forms in a language contact framework. Altogether, the papers provide a lively illustration of and a fairly representative selection from ongoing high-quality linguistic research into American English.